THE DETERMINATION OF SALINITY AND NUTRITION (NaH2PO4) PROFILE IN Nannochloropsis oculata CULTIVATION TO GAIN MAXIMUM LIPID - Elida Purba; Kenjiro Siburian (Reaktor, 2012)
The determination of salinity and nutrition (NaH2PO4) profile in Nannochloropsis oculata cultivationto gain maximum lipid was investigated. The purpose of this research was to determine the optimumsalinity and nutrition (NaH2PO4) to gain maximum lipid in Nannochloropsis oculata. Phosphor canbe obtained by adding NaH2PO4 and a salinity enhancement can be applied by adding NaCl to theculture. This research was run by matching each variable of salinity (33, 34, 35, and 36 ppt) to eachvariable of NaH2PO4 (5, 10 and 15 ppm) randomly. The results show that the percentage of maximumlipid in Nannochloropsis oculata was obtained at 35 ppt and 5 ppm NaH2PO4 (37.68 %). Neverthelessthe maximum lipid percentage is low and it can be caused by some factors, such as the dryingtemperature for preparing the dry microalgae to extract, the cell disruption method and the extractionsolvent used. By seeing the results, salinity can affect the total lipid in Nannochloropsis oculata. Thegreater the salinity in culture the greater the lipid content in Nannochloropsis oculata. Otherwise adifferent response was obtained by adding NaH2PO4. If NaH2PO4 concentration is greater, the lipidcontained Nannochloropsis oculata will be lower Penentuan profilsalinitas dan nutrisi (NaH2PO4) pada pembiakan Nannochloropsis oculata untuk memperoleh lipidmaksimum diteliti. Tujuan penelitian ini adalah untuk menentukan salinitas dan nutrisi (NaH2PO4)optimum untuk memperoleh lipid maksimum pada Nannochloropsis oculata. Fosfor dapat diperolehdengan menambahkan NaH2PO4 pada kultur dan peningkatan salinitas dapat dilakukan denganmenambahkan NaCl pada kultur. Penelitian ini dijalankan dengan mencocokkan setiap variabelsalinitas (33, 34, 35, dan 36 ppt) dengan setiap variabel NaH2PO4 (5, 10 dan 15 ppm) secara acak.Hasil menunjukkan bahwa persentase lipid maksimum pada Nannochloropsis oculata diperoleh padasalinitas 35 ppt dan 5 ppm NaH2PO4 (37,68 %). Walaupun demikian, persentase lipid maksimummasih tergolong rendah dan hal ini dapat disebabkan oleh beberapa faktor, seperti temperaturpengeringan yang diterapkan, metode cell disruption dan pelarut ekstraksi yang digunakan. Denganmempelajari hasil yang telah didapat, salinitas dapat mempengaruhi lipid total padaNannochloropsis oculata. Semakin tinggi salinitas pada biakan, semakin tinggi kandungan lipid padaNannochloropsis oculata. Sebaliknya didapatkan respon yang berbeda saat menambahkan NaH2PO4.Apabila konsentrasi NaH2PO4 semakin tinggi, maka lipid yang terkandung pada Nannochloropsisoculata akan menjadi lebih rendah.